STUDI SIFAT FISIK DAN SIFAT MEKANIK KOMPOSIT EPOXY-ZIRCONIA - , Yohanes Suyoko; , Ir. M. Waziz Wildan, M.Sc., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Composites can be defined as a combination of two or more materials that differ in macroscopic scale to produce a new material with properties that are not attainable with their constituent materials. Particulate composites consist of a matrix reinforced with a dispersed phase in form of particles. This research aims to investigate the influence of zirconia particles in an epoxy matrik on the tensile strength, bending strength, fracture thoughness, impact toughness, abrasiveness and relative density of epoxy-zirconia composites. Materials used in this research were epoxy as matrix and zirconia as reinforcement. Epoxy resin (with a code of DGEBA DER 331) was obtained from DOW Chemical England. Zirconia particles was obtained from Goodfellow Cambridge Ltd UK. Hardener with a type of 2,4,6-Tris (Dymethilaminomethyl) phenol 95% was purchased from Sigma Aldrich England. Prior to use, the zirconia powder was heated up at 100° C for 2 hour. Composites were produced with various amount of zirconia powder of 0, 10, 20 and 30%wt mixed with 98:2 epoxy-hardener weight ratio. Each composition of epoxy and zirconia powder was mixed and stirred mechanically with 800 rpm at 80°C for 1 hour. During that stirring, the hardener was added at last minute. The mixture was then placed in a vacuum chamber for 1 minute to remove the bubble, and it was followed by pouring the mixture into an aluminium mould. The mould with the mixture contents were cured in an oven at 80°C for 1 hour. Post curing of the composites was performed at 120°C for 2 hour. The specimens were then examined using tensile test, three-point bending test, fracture toughness test, Charpy impact test, abrasive test and density test. The microstructures and fracture surfaces were observed using digital photograph, optical microscope and Scanning Electron Microscope. The result shows that composites with 10 wt% of zirconia was found to be the optimum values in tensile strength, flexural strength, flexural modulus, impact toughness and specific abrasion i.e., 83.69 MPa, 138.86 MPa, 3,641.66 MPa, 3.84 kJ/m2 and 2.38 x 10-7mm²/kg, respectively. The fracture toughness and relative density of the composites were decreased with increasing of zirconia contents.